2002
DOI: 10.1016/s0168-6496(02)00282-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of alkane monooxygenase genes in Arctic and Antarctic hydrocarbon-contaminated and pristine soils

Abstract: The prevalence of four alkane monooxygenase genotypes (Pseudomonas putida GPo1, Pp alkB; Rhodococcus sp. strain Q15, Rh alkB1 and Rh alkB2; and Acinetobacter sp. strain ADP-1, Ac alkM) in hydrocarbon-contaminated and pristine soils from the Arctic and Antarctica were determined by both culture-independent (PCR hybridization analyses) and culture-dependent (colony hybridization analyses) molecular methods, using oligonucleotide primers and DNA probes specific for each of the alk genotypes. PCR hybridization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
86
0
6

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(107 citation statements)
references
References 31 publications
15
86
0
6
Order By: Relevance
“…A study on a similar creosote-contaminated site in Sweden, however, reported a decline in actinobacterial populations (assessed by phospholipid fatty acid analysis) from the hot spots of pollution (Tö rneman et al, 2008). Several investigations on hydrocarbon-contaminated cold sites have also demonstrated the dominance of Proteobacteria over Actinobacteria (Whyte et al, 2002;Margesin et al, 2003;Labbe et al, 2007;Ringelberg et al, 2008). Our findings suggest that among both groups of robust degraders, Actinobacteria were outcompeted by Proteobacteria in this aged creosote-polluted site.…”
Section: Discussionsupporting
confidence: 44%
“…A study on a similar creosote-contaminated site in Sweden, however, reported a decline in actinobacterial populations (assessed by phospholipid fatty acid analysis) from the hot spots of pollution (Tö rneman et al, 2008). Several investigations on hydrocarbon-contaminated cold sites have also demonstrated the dominance of Proteobacteria over Actinobacteria (Whyte et al, 2002;Margesin et al, 2003;Labbe et al, 2007;Ringelberg et al, 2008). Our findings suggest that among both groups of robust degraders, Actinobacteria were outcompeted by Proteobacteria in this aged creosote-polluted site.…”
Section: Discussionsupporting
confidence: 44%
“…Shifts in bacterial communities in response to hydrocarbon contamination have been reported in several Antarctic soils (Aislabie et al 1998;Whyte et al 2002;Saul et al 2005). Soils in the Ross Sea region contaminated with alkanes and polyaromatic hydrocarbons were found to have higher counts of cultureable heterotrophic bacteria and lower bacterial diversity than uncontaminated control soils (Saul et al 2005).…”
Section: Exogenous Factors and Inputsmentioning
confidence: 89%
“…Alaskan sediments Colony hybridization with alkB 39% of viable heterotrophs from uncontaminated soil contain alkB gene probe 67% of viable heterotrophs from contaminated soil contain alkB [97] Contaminated soil PCR followed by Southern blot Detection and quantification of alkB (and other genes) in soil: 1-10 with alkB gene probe gene copies per gram of soil can be detected [98 Variety of cold ecosystems PCR, and Southern blots None of the psychrophilic alkane degraders possess genes with alkB gene probe with high homology to P. putida alkB [99] Fuel oil-contaminated site Dot-blots DNA extracted from soil shows no significant hybridization with an alkB-gene probe [100] Shallow aquifer Southern blots 10-20% of the total bacterial community hybridizes with alkB gene probe with an alkB gene probe [101] Various sources PCR with highly degenerate Most alkane-degrading strains contain distantly related alkB homologs (54 bacterial strains) primers for alkB homologs (homology not sufficient for Southern or dot-blots) [50] Shallow aquifer Dot-blots with DNA extracted alkB genotypes start at 11% of total community, and peak at (natural attenuation site) from aquifer samples 52% after injection of synthetic jet fuel in the aquifer [102] Various sources Southern, colony and dot-blots, alkB genes (close homologs) are widespread only in short-chain n-alkane (54 bacterial strains) PCR followed by Southern degrading pseudomonads [76] Rhizosphere vs. bulk soil Multiplex PCR At a contaminated site alkB was 10 times more prevalent in the endophytic community compared to the bulk soil community [103] Propane and butaneDot-blots 8 of 15 strains (including pseudomonads and rhodococci) utilizing bacteria gave a strong signal, and 7 a weak signal with the IMT37 gene [37] Land treatment unit (LTU) PCR, terminal restriction alkB increased in abundance during the first 3 weeks of LTU operation, fragment length polymorphism and comprised > 80% of the total PCR products [104] Arctic and Antarctic soil PCR-hybridization Rhodococcal alkB genes occur in contaminated and pristine soils, and colony hybridization P. putida alkB occurs more frequently in contaminated soils [105] similar genes in other butane degraders (pseudomonads, rhodococci and unidentified bacteria). In a dot-blot experiment, 8 out of 15 propane or butane-degrading bacteria gave a strong signal with the gene-probe, while the remaining 7 gave a weak but detectable signal [37].…”
Section: Environment/source Methods Conclusion For Alkb Homologs Refmentioning
confidence: 99%